Integrating online and postal services in Vietnam’s public administration - Duong Quoc Chinh; Nguyen Thi Thu Cuc (Journal of State Management, 2025)
In the digital era, governments worldwide - including Vietnam - have actively embraced digital technology to enhance the quality and efficiency of public administrative service delivery. Nevertheless, disparities in technology access among regions and social groups remain a significant challenge, particularly in developing countries. To ensure equity and that no one is left behind, Vietnam has implemented a service-delivery model that combines online public services with public postal services. This approach improves service effectiveness while ensuring integration and timely feedback. The article analyzes how Vietnam leverages this hybrid method to overcome accessbarriers faced by vulnerable groups and offers recommendations for building an efficient, equitable,and inclusive model of public administrative service delivery in the context of digital transformation.